On the origins of welfare stigma: Comparing two social assistance schemes in rural China - Li, M; Walker, R (SAGE Publications, 2017)
While stigma has often been implicated in the low take-up of benefits, its aetiology is not well understood. Drawing distinctions from earlier research, notably differentiating personal, social and institutional stigma, the article explores how each is related to each other and how each alone, and in concert, is framed by political and local culture. As case-studies, two of the world’s largest social assistance schemes, Dibao and Wubao, are compared in a village in south central China based on ethnographic work with recipients, village cadre charged with implementing both schemes, and non-recipients. In explaining the reasons for the very different level of stigma attaching to each scheme, the article unearths processes of salience to academics and policymakers.